Escape of farmed tilapiines into the wild and entry of wild forms in fishponds, and the possible interactions between wild and farmed tilapiines from a sample of smallholder farms in Central Uganda - Tenywa Mwanja, Matthew; Waiswa Mwanja, Wilson (African Journal of Ecology, 2009)
Seven smallholder fishponds in central Uganda were studied between 2000 and 2001 to investigate the interaction of farmed tilapiines with their wild conspecifics. Emphasis was on the features that facilitate escape of fish and ⁄ or entry of fish into the farms and interactions between the farmed and the wild. These included number of species, source of seed, connection between pond and natural watercourses, purpose of the farm, destination of cultured fish and interaction between farmed and wild fish. Fishponds had no screens against entry of wild fish into the farm or escape of farmed fish into the wild and occurred within wetlands close to natural watercourses. Ponds stocked with one fish species were found to have multispecies with some individuals that were apparently intermediate morphs between the species. Fry produced within the growout fishponds was shared with other farmers within and outside the watersheds. This study showed that smallholder farms with little or no control of escape or entry of fish out and into the fishponds, and little or no management present circumstances that facilitate continued movement of tilapiines within and across watersheds in Ugandan waters. The study also indicated possible genetic interaction between farmed and their wild conspecifics through interactions within fishponds.
Keywords: Ecological interactions; Farmed tilapiines; Wild fish